2019
DOI: 10.1097/mao.0000000000002092
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Vestibular Evoked Myogenic Potentials in Menière's Disease: A Comparison of Response Metrics

Abstract: Objective: The cervical vestibular evoked myogenic potential (cVEMP) has been used to evaluate patients with Meniere's Disease (MD). Studied cVEMP metrics include: amplitude, threshold, frequency tuning and interaural asymmetry ratio (IAR). However, few studies compared these metrics in the same set of MD patients, and methodological differences prevent such a comparison across studies. This study investigates the value of different cVEMP metrics in distinguishing one set of MD patients from age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The abnormal response to different frequencies and the normalized p13–n23 amplitude and VEMP inhibition depth have been considered a good marker of Ménière`s disease for the detection of suspected asymptomatic hydrops in the saccule [ 5 ]. This finding has also been obtained to a lesser degree in the unaffected ear of a small group of patients with unilateral MD [ 6 ].…”
Section: Introductionsupporting
confidence: 66%
“…The abnormal response to different frequencies and the normalized p13–n23 amplitude and VEMP inhibition depth have been considered a good marker of Ménière`s disease for the detection of suspected asymptomatic hydrops in the saccule [ 5 ]. This finding has also been obtained to a lesser degree in the unaffected ear of a small group of patients with unilateral MD [ 6 ].…”
Section: Introductionsupporting
confidence: 66%
“…In case of implantation of otolith structures, cVEMP and oVEMP responses should be absent bilaterally. Although the otolith system can probably have a gradual decline in function and does not work as an “on-off” system [ 52 ], VEMPS are not currently clinically suited to detect subtle changes in otolith function or define “minimal residual otolith function”. It was decided therefore that otolith implantation should only be performed in patients with bilaterally absent VEMP responses and not take into account other parameters, e.g.…”
Section: Commentsmentioning
confidence: 99%
“…(2017) studied 42 patients with certain unilateral MD and 21 healthy controls and reported that multi-frequency VEMPs analysis offers a simple and cost-effective method to address the diagnostic difficulties presented by MD. Noij et al. (2019) showed that the cervical VEMPs metrics most useful in distinguishing definite MD patients from healthy controls are VEMPs threshold, VEMPs -normalized peak-to-peak amplitude, and VEMPs inhibition depth.…”
Section: Discussionmentioning
confidence: 99%